Clinical Oral Disorders in Adults Screening Protocol (CODA‐SP) from the 2019 Vancouver IADR Consensus Symposium. (2nd October 2020) - MacEntee, Michael I.; Brondani, Mario; Avivi‐Arber, Limor; Bartlett, David; Donnelly, Leeann; Duyck, Joke; Hori, Kazuhiro; Karve, Avanti; Persson, G. Rutger; Kettratad‐Pruksapong, Matana; Schimmel, Martin; Hon‐ching So, Frankie; et al.
Abstract: Background: The Clinical Oral Disorder in Elders (CODE) index was proposed in 1999 to assess the oral health status and treatment needs of older people who typically were edentate or had few natural teeth. Since then, more people are retaining natural teeth into old age and have oral disorders similar to younger adults. In addition, there has been further guidance on screening for disease that includes changes to the clinical indicators of several oral disorders and greater sensitivity to people's concerns about their oral health and care needs. Methods: Experts in dental geriatrics assembled at a satellite symposium of the International Association of Dental Research in June 2019 to revise the objectives and content of the CODE index. Before the symposium, 139 registrants were asked for comments on the CODE index, and 11 content experts summarised current evidence and assembled reference lists of relevant information on each indicator. The reference lists provided the base for a narrative review of relevant evidence supplemented by reference tracking and direct searches of selected literature for additional evidence. Results: Analysis of the evidence by consensus of the experts produced the Clinical Oral Disorders in Adults Screening Protocol (CODA‐SP). Conclusions: The CODA‐SP encompasses multiple domains of physical and subjective indicators with weighted severity scores. Field tests are required now to validate its effectiveness and utility in oral healthcare services, outcomes and infrastructure.